2022
DOI: 10.3389/fchem.2022.909250
|View full text |Cite
|
Sign up to set email alerts
|

Non-Palladium-Catalyzed Oxidative Coupling Reactions Using Hypervalent Iodine Reagents

Abstract: Transition metal-catalyzed direct oxidative coupling reactions via C–H bond activation have emerged as a straightforward strategy for the construction of complex molecules in organic synthesis. The direct transformation of C–H bonds into carbon–carbon and carbon–heteroatom bonds renders the requirement of prefunctionalization of starting materials and, therefore, represents a more efficient alternative to the traditional cross-coupling reactions. The key to the unprecedented progress made in this area has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…These reagents are potential oxidants due to their excellent oxidizing and electrophilic properties [ 9 , 10 , 11 , 12 , 13 ]. The unique characteristics attributed to these reagents are non-toxicity, easy handling, high reactivity and stability, combined with good site selectivity and broad applicability in several synthetic transformations [ 14 , 15 , 16 ]. Therefore, hypervalent iodine reagents are of paramount importance to organic chemistry for the development of new asymmetric and non-asymmetric reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These reagents are potential oxidants due to their excellent oxidizing and electrophilic properties [ 9 , 10 , 11 , 12 , 13 ]. The unique characteristics attributed to these reagents are non-toxicity, easy handling, high reactivity and stability, combined with good site selectivity and broad applicability in several synthetic transformations [ 14 , 15 , 16 ]. Therefore, hypervalent iodine reagents are of paramount importance to organic chemistry for the development of new asymmetric and non-asymmetric reactions.…”
Section: Introductionmentioning
confidence: 99%
“…16–19 In addition, a serious problem associated with transition-metal-promoted reaction is the product contamination, which is not observed with iodine( iii / v ) reagents. Therefore, hypervalent iodine compounds are potential rivals to transition metals in many organic reactions as covered in several excellent review articles, 20–30 book chapters, and books. 31–39…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In addition, a serious problem associated with transition-metal-promoted reaction is the product contamination, which is not observed with iodine(III/V) reagents. Therefore, hypervalent iodine compounds are potential rivals to transition metals in many organic reactions as covered in several excellent review articles, [20][21][22][23][24][25][26][27][28][29][30] book chapters, and books. [31][32][33][34][35][36][37][38][39] Traditionaly, hypervalent iodine reagents are employed as stoichiometric reagents but recent studies have revealed their use as versatile catalysts, as reviewed by Singh, Wirth, and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…The C-H arylation of arenes, heteroarenes, alkenes, and alkanes by diaryliodonium salts has been achieved using a variety of different metal salts as catalysts; representative examples with some or all of these substrates are known with Pd [5], Pt, Au, Cu, Fe, Ir, Ni, and Ru salts [6]. Diaryliodonium salts are also known to arylate a wide variety of nucleophiles such as enolates, carboxylates, amides, alkoxides, halides, etc.…”
Section: Introductionmentioning
confidence: 99%